Corrigendum to ?Green synthesis of biodiesel from Citrus medica seed oil using green nanoparticles of copper oxide? [Fuel 323 (2022) 124285] (Fuel (2022) 323, (S0016236122011371), (10.1016/j.fuel.2022.124285)) - Rozina; Reen Chia S.; Ahmad M.; Sultana S.; Zafar M.; Asif S.; Bokhari A.; Nomanbhay S.; Mubashir M.; Shiong Khoo K.; Show P.L. (Elsevier Ltd, 2025)
The authors regret to inform that the following error was overlooked in their article. In this article there was an error in Fig. 7. Figure 7b which represents the 13CNMR of Citrus medica biodiesel on page 10 and the associated paragraph in section 3.4.2. NMR spectroscopic analysis of the article body on page 9 is replaced by the following:[Formula presented] Fig. 7. (b) 13CNMR of Citrus medica. The 13CNMR spectrum of CMBD has been depicted in Fig. 7b which illustrates the structural characteristics of synthesized methyl ester. The signal for ester carbonyl (COO ) group appeared at 174.26 ppm whereas, the characteristic methoxy carbon signal (O CH3) was observed at 51.40 ppm. The signal at 129.71 to 130.15 ppm was assigned to unsaturated and outer non-conjugated (CH CH-CH2-CH CH ) carbons. Inner carbons of non-conjugated (CH CH-CH2-CH CH ) appeared at 127.88 ppm. Signals for aliphatic methylene carbons (CH2-s) of long carbon chain appeared at 27.19 to 31.91 ppm. Moreover, the signal for (C O) carbon group appeared at 76.63 to 77.48 ppm. The total conversion of Citrus medica seed oil into methyl ester was calculated using Eq. (7) and found to be 92%, which is near to obtained experimental yield (93%). The authors would like to apologise for any inconvenience caused. ? 2024 Elsevier Ltd